2002
DOI: 10.1074/jbc.m109756200
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Subunit c of the Vacuolar ATPase Confer Resistance to Bafilomycin and Identify a Conserved Antibiotic Binding Site

Abstract: Bafilomycin A1, a potent inhibitor of vacuolar H؉ -ATPases (V-ATPase), inhibited growth of Neurospora crassa in medium adjusted to alkaline pH. Ninety-eight mutant strains were selected for growth on medium (pH 7.2) containing 0.3 or 1.0 M bafilomycin. Three criteria suggested that 11 mutant strains were altered in the V-ATPase: 1) these strains accumulated high amounts of arginine when grown at pH 5.8 in the presence of bafilomycin, 2) the mutation mapped to the locus of vma-3, which encodes the proteolipid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
100
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(106 citation statements)
references
References 36 publications
3
100
1
2
Order By: Relevance
“…Autoradiographies of gels after exposition to a phosphoscreen (lanes 2, 4, and 6). explain the discrepancy between this result and the results obtained with N. crassa mutants, which exhibited a higher tolerance to bafilomycin but not to concanamycin (10). Because labeling was not impaired by salicylihalamide, we conclude that the site(s) and mechanism of inhibition for benzolactone enamides may be different from that for plecomacrolides.…”
Section: Revised Purification Protocol Reveals Subunit a In The Insectcontrasting
confidence: 56%
See 1 more Smart Citation
“…Autoradiographies of gels after exposition to a phosphoscreen (lanes 2, 4, and 6). explain the discrepancy between this result and the results obtained with N. crassa mutants, which exhibited a higher tolerance to bafilomycin but not to concanamycin (10). Because labeling was not impaired by salicylihalamide, we conclude that the site(s) and mechanism of inhibition for benzolactone enamides may be different from that for plecomacrolides.…”
Section: Revised Purification Protocol Reveals Subunit a In The Insectcontrasting
confidence: 56%
“…In the presence of 1 mM DCCD the V-ATPase did not bind to the column, indicating that the binding site for bafilomycin is near the binding site(s) for DCCD and may thus be located in the proteolipid, subunit c. However, because DCCD, especially at the rather high concentration of 1 mM, may bind to sites different from that in the proteolipid and may bind not only to carboxyl groups but also to sulfhydryl groups or to tyrosine residues (9), and since the 100-kDa subunit a was not clearly resolved in this study, the bafilomycin binding subunit was still not identified. Strong hints in favor of subunit c representing the bafilomycin binding subunit were provided by recent results from analysis of Neurospora crassa strains, indicating that those with point mutations in subunit c show a higher tolerance to bafilomycin (I 50 80 -400 nM) compared with the wild type (I 50 6.3 nM); interestingly, the tolerance to concanamycin was not changed simultaneously (10).…”
mentioning
confidence: 96%
“…Although sufficient quantities of streptavidin-biotin-bafilomycin were not available to perform the cytoplasmic pH and proton flux experiments described above, we assessed ATP-dependent proton transport in vacuolar membranes isolated from yeast in the presence and absence of this compound. Bafilomycin binds to the V-ATPase at a site within the ring of c subunits (36). We expected that when bound to streptavidin, biotin-bafilomycin would be able to inhibit activity from the luminal (or extracellular) surface but because of steric interference between streptavidin and the V 1 domain would be unable to inhibit the pump from the cytoplasmic surface.…”
Section: Treatment Of Mb231 Cells With a Membrane-impermeable Form Ofmentioning
confidence: 99%
“…V 0 forms a membranespanning proton-translocating complex; in yeast, it is composed of at least five different subunits termed a, c, cЈ, cЉ, and d, of which subunit c binds bafilomycin A 1 , a specific inhibitor of V-ATPases (5)(6)(7)(8). The V 1 sector is attached to the cytoplasmic side of the V 0 sector, consists of at least eight different subunits termed A-H, and contains catalytic and noncatalytic ATPbinding sites.…”
mentioning
confidence: 99%